DAKWAH DAN PROBLEMATIKA STUDI HADIS - Kamarudin Kamarudin (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
Hadith is the second source of Islamic law after the Quran, hich every Moslem should follow it as a guide and uswah in life and living. On the other hand, the tradition has its own problems among Mosle!T13, even some of those who opposed its use as a legal law. This issue is a challenge for preachers because the Quran and Sunnah or ljadith are two sources of law are complementary and mutually explain in easy to understand and apply the teachings of Islam. Therefore,da'wah should have a strategy to reconcile the good people of the wrong understanding of tradition as well as the attitude of rejection of /fadith (opposed Sunnah) itself so worried will eliminate the use of lfadith in the future.